Characterization of pecan PEBP family genes and the potential regulation role of CiPEBP-like1 in fatty acid synthesis - Wang, Jiani (Plant science : an international journal of experimental plant biology, 2025)
Copyright © 2024 Elsevier B.V. All rights reserved.